Melatonin and diabetes: from pathophysiology to the treatment perspectives - Vladimir Iosifovich Konenkov (Endocrinology Research Centre, 2013)
Pineal hormone melatonin synchronizes insulin secretion and glucose homeostasis with solar periods. Misalliance between melatonin-mediated circadian rhythms and insulin secretion characterizes diabetes mellitus type 1 (T1DM) and type 2 (T2DM). Insulin deficiency in T1DM is accompanied by increased melatonin production. Conversely, T2DM is characterized by diminished melatonin secretion. In genome-wide association studies the variants of melatonin receptor MT2 gene (rs1387153 and rs10830963) were associated with fasting glucose, beta-cell function and T2DM. In experimental models of diabetes melatonin enhanced beta-cell proliferation and neogenesis, improved insulin resistance and alleviated oxidative stress in retina and kidneys. However, further investigation is required to assess the therapeutic value of melatonin in diabetic patients.